Treatment options for unresectable hepatocellular carcinoma - Catarina Budyono; Ainun Fatiha DP; Baiq Aliza K.I; I Gede Prabananda A (Faculty of Medicine Universitas Mataram, 2022)
Hepatocellular carcinoma (HCC) is a primary liver cancer that occurs due to the abnormal growth of hepatocytes. HCC is one of the cancers with the highest prevalence and incidence in the world. The main risk factors for HCC in Indonesia are chronic infection with hepatitis B virus, hepatitis C virus, and liver cirrhosis. The selection of the appropriate treatment modality for each patient is based on several patient-specific characteristics, such as tumor size, location, portal vein thrombosis, and liver function. Treatment options for unresectable hepatocellular carcinoma include intra-arterial therapy, multikinase inhibitors, and immunotherapy. Determining the stage is an important part of managing HCC because it can determine the treatment. One of the staging systems is the Barcelona Clinic Liver Cancer (BCLC) which categorizes HCC into 5 stages. Clinical severity criteria with BCLC stage are often used because they have good validity in predicting the prognosis of HCC patients.